2021
DOI: 10.1038/s41467-021-22441-4
|View full text |Cite
|
Sign up to set email alerts
|

Mediator subunit Med15 dictates the conserved “fuzzy” binding mechanism of yeast transcription activators Gal4 and Gcn4

Abstract: The acidic activation domain (AD) of yeast transcription factor Gal4 plays a dual role in transcription repression and activation through binding to Gal80 repressor and Mediator subunit Med15. The activation function of Gal4 arises from two hydrophobic regions within the 40-residue AD. We show by NMR that each AD region binds the Mediator subunit Med15 using a “fuzzy” protein interface. Remarkably, comparison of chemical shift perturbations shows that Gal4 and Gcn4, two intrinsically disordered ADs of differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 57 publications
1
46
1
Order By: Relevance
“…We also note that electron density for the RBR loop was not as well defined as other parts of the protein (Figure S4A), suggesting conformational flexibility in the interface. Intriguingly, residues located within the RBR loop and near the interface are highly hydrophobic (Figure 3A), suggesting that H-H dimerization is driven by a collection of hydrophobic interactions, reminiscent of “fuzzy” interactions shown for other TFs (Pricer et al, 2017; Tuttle et al, 2021). It is noteworthy that the RBR loop is also involved in crystallographic packing (Figures S4A, S4B), likely involving similarly fuzzy, hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…We also note that electron density for the RBR loop was not as well defined as other parts of the protein (Figure S4A), suggesting conformational flexibility in the interface. Intriguingly, residues located within the RBR loop and near the interface are highly hydrophobic (Figure 3A), suggesting that H-H dimerization is driven by a collection of hydrophobic interactions, reminiscent of “fuzzy” interactions shown for other TFs (Pricer et al, 2017; Tuttle et al, 2021). It is noteworthy that the RBR loop is also involved in crystallographic packing (Figures S4A, S4B), likely involving similarly fuzzy, hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 98%
“…Despite its importance in immune homeostasis, molecular functions of FoxP3 remain poorly understood. For examples, it is highly debated whether FoxP3 is a transcriptional activator or suppressor, or can be both depending on the target genes (Zheng et al, Nature, 2007;Arvey et al, 2014;Kwon et al, 2017;Li et al, 2007;Zemmour et al, 2021); and which of the genes affected by FoxP3 are the direct target genes versus those regulated indirectly, perhaps mediated by FoxP3's direct target genes (Ricardo N. Ramirez, In Press;van der Veeken et al, 2020;Zemmour et al, 2021). It is also unclear how FoxP3 alters the target gene expression as FoxP3 binds predominantly to genomic loci that have pre-established chromatin accessibility and induces little change in the accessibility of the bound sites van der Veeken et al, 2020;Yoshida et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were unable to reproducibly detect interaction between SOX15 and SCCs in SOX15-HA knockin mouse ESC extracts by coimmunoprecipitation. We surmise that it could be due to the low expression level of SOX15 (see Figure 1B) and the often weak and transient nature of functional coactivator-activator interactions (31) Therefore, we tested SOX15-SCCs interactions by performing transient transfection and coimmunoprecipitation in 293T cells. We found that SOX15, like SOX2, binds XPC, DKC1, and ABCF1 (Figure 1E) (13, 15, 32, 33).…”
Section: Resultsmentioning
confidence: 99%
“…Few structural details of TF–Mediator interactions are available, owing to the disorder and dynamics of TF activation domains . Available evidence shows that TF activation domains retain their disorder even upon Mediator binding, adopting a so-called fuzzy interface 85 . By contrast, the TF-binding surface of Mediator is structured, at least in reported cases.…”
Section: Mediator–tf Reciprocal Regulationmentioning
confidence: 99%